2020
DOI: 10.1109/access.2020.3007076
|View full text |Cite
|
Sign up to set email alerts
|

Motion Sickness in Virtual Reality: An Empirical Evaluation

Abstract: Due to rapid growth in Virtual Reality (VR) technology, the industry of VR is expected to grow around $26.89 billion by 2022. However, with its extensive growth and immersive inclusion in human life, health-related issues are reported including, but not limited to nauseated feeling, vomiting, dizziness and cold sweats. These issues introduce a well-known side effect termed as motion sickness in VR users. Consequently, motion sickness limits the VR community in the full adaptation of this immersive technology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 38 publications
(86 reference statements)
2
40
3
3
Order By: Relevance
“…To figure out what factors influence motion sickness in VR, Chattha et al [ 9 ] conducted an experiment with 46 participants. The VR system used in this study was the Oculus Rift DK2.…”
Section: Introductionmentioning
confidence: 99%
“…To figure out what factors influence motion sickness in VR, Chattha et al [ 9 ] conducted an experiment with 46 participants. The VR system used in this study was the Oculus Rift DK2.…”
Section: Introductionmentioning
confidence: 99%
“…Unintended consequences may occur from a poor design that does not account for personal safety and minimize risk. These may include physiological effects such as visual fatigue (Iskander et al, 2018) and motion sickness (Chattha et al, 2020), which studies have shown to affect women more than men (e.g., Kim et al, 2018); or the introduction of physical danger that may even turn out to be life threatening. For instance, distraction or impaired attention may create physical danger for an AR game in which players drive automobiles while playing the game (Ayers et al, 2016), walk around one's city, or are even mistook as threats by uninformed observers.…”
Section: Low Vs High Ethical Considerationmentioning
confidence: 99%
“…The assessment survey questionnaire was completed after the given participant finished work on a given day. The cyber sickness survey was completed on a similar basis, except that if clear symptoms [27] occurred while using the application, the test would be discontinued at the participant's request and the questionnaire completed. If there were no clear symptoms or signals from the participant, both questionnaires were completed at the end of the workday.…”
Section: A Post-testmentioning
confidence: 99%